(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The objective of the present study was to investigate the verbal behavior of a 49-year-old man who had been diagnosed as chronical schizophrenic since he was 20 years old. The intervention was implemented in two response classes: psychotic speeches and appropriate speeches. The procedures of differential reinforcement of alternative behaviors and extinction were conducted by research assistants in 45-minute sessions, twice a week. Experimental control was obtained through an ABAB reversal design followed by Follow-up. All sessions were video recorded for posterior data reliability calculation. The study results show a reduction of psychotic speeches and an increase in appropriate speeches during intervention sessions. The data demonstrate that the verbal behavior of a person diagnosed as schizophrenic can be controlled by social reinforcement combined with extinction. Delusion and hallucinations were discussed as verbal behavior.